Comparative evaluation of dental and cephalometric skeletal characteristics in the sagittal and vertical plane - Cheong, Joo Ming; Zaharul, Fatin Nabihah; Abdul Hamid, Hanis Izzati; Mohd Ibrahim, Mohamad Shafiq (International Islamic University Malaysia, 2024)
PURPOSE: This study aims to enumerate the prevalence of skeletal and dental classifications in a sample of Malay adult patients, and to determine the association between sagittal skeletal relationship, vertical facial dimension and anteroposterior molar relationship.